2015
DOI: 10.1007/s10995-015-1746-6
|View full text |Cite
|
Sign up to set email alerts
|

Folate and Vitamin B12 Deficiency Among Non-pregnant Women of Childbearing-Age in Guatemala 2009–2010: Prevalence and Identification of Vulnerable Populations

Abstract: Introduction Information on folate and vitamin B12 deficiency rates in Guatemala is essential to evaluate the current fortification program. The objectives of this study were to describe the prevalence of folate and vitamin B12 deficiencies among women of childbearing age (WCBA) in Guatemala and to identify vulnerable populations at greater risk for nutrient deficiency. Methods A multistage cluster probability study was designed with national and regional representation of nonpregnant WCBA (15–49 years of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 23 publications
4
18
1
Order By: Relevance
“…Also, we observed lower RBC folate and/or plasma vitamin B-12 concentrations in urban areas, among WCBA of Mayan origin, and in the West and South regions. These results were consistent with published results from Guatemala, other Latin American countries, and the United States (3540), where variability of blood folate and vitamin B-12 concentrations within the population, as well as across racial and ethnic groups and regions, was observed. These differences could be explained in part by cultural differences and/or differences in access to or availability of fortified wheat flour for vulnerable populations (35).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Also, we observed lower RBC folate and/or plasma vitamin B-12 concentrations in urban areas, among WCBA of Mayan origin, and in the West and South regions. These results were consistent with published results from Guatemala, other Latin American countries, and the United States (3540), where variability of blood folate and vitamin B-12 concentrations within the population, as well as across racial and ethnic groups and regions, was observed. These differences could be explained in part by cultural differences and/or differences in access to or availability of fortified wheat flour for vulnerable populations (35).…”
Section: Discussionsupporting
confidence: 92%
“…National serum and RBC folate and vitamin B-12 concentrations among nonpregnant WCBA in our study were similar to or slightly lower than those reported from the postfortification period in Guatemala (28 compared with 30 nmol/L, 719 compared with 725 nmol/L, and 233 compared with 341 pmol/L, respectively) (35). Also, we observed lower RBC folate and/or plasma vitamin B-12 concentrations in urban areas, among WCBA of Mayan origin, and in the West and South regions.…”
Section: Discussionsupporting
confidence: 85%
“…Colombia passed folic acid food fortification legislation in 1996 [16], but our data were collected after fortification was implemented, so we cannot determine whether deaths due to neural tube defects decreased after implementation. Therefore, it would be important to collect other data to assess whether rates of neural tube defects have reached optimal levels achievable through food fortification [17] across all population groups [18]. …”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no global data are available on the prevalence of folate deficiency worldwide, although the deficiency has been detected in countries as different as Burkina Faso, Guatemala, Iran, Ireland, Thailand and United States (Arsenault et al, 2014;Assantachai and Lekhakula, 2007;Brunst et al, 2014;Harrington et al, 2008;Rosenthal et al, 2015;Sedehi, 2013 …”
Section: -1-folate Requirementsmentioning
confidence: 99%
“…In an urban US population, Brunst et al (2014) estimated that 16% of pregnant women have inadequate folate intake. Analyses of the serum level of folate in women of childbearing age showed that 5.1% of women in Guatemala and around 30% of women in Iran had folate deficiency (Rosenthal et al, 2015;Sedehi, 2013). In Thailand, Assantachai and Lekhakula (2007) evaluated the serum level of folate of subjects aged 60 years and over, and detected folate deficiency in 39% of this population group.…”
Section: Accepted Manuscriptmentioning
confidence: 99%